1993
DOI: 10.1136/gut.34.9.1171
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed gastric emptying in the short bowel syndrome. Evidence for a 'colonic brake'.

Abstract: Gastric emptying of liquid (orange juice containing technetium-99m ('Tc) labelled antimony sulphide colioid) and solid (570 kcal pancake containing O 5 mm resin microspheres labelled with Indiun-ll ("'-In)) was measured in seven patients with jejunum and no colon (jejunal lengths 30-160 cm), six patients with jejunum in continuity with the colon (jejunal length 25-75 cm), and in 12 normal subjects. In patients with no colon early emptying of liquid was rapid (median 25% emptying: 7 v 25 min, no colon v normal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 31 publications
0
62
0
4
Order By: Relevance
“…36,37 GLP-2 is secreted from the intestinal mucosa in response to food ingestion, and we recently found that postprandial GLP-2 secretion is impaired in patients with no terminal ileum and no colon. 17 The well-known concomitant poor intestinal adaptation 14 and the rapid gastric and intestinal transit described in these patients who have jejunostomies 15,16 prompted us to evaluate the effect of GLP-2 in this subgroup of short-bowel patients. As expected, none of the patients studied had a preserved meal-stimulated GLP-2 response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 GLP-2 is secreted from the intestinal mucosa in response to food ingestion, and we recently found that postprandial GLP-2 secretion is impaired in patients with no terminal ileum and no colon. 17 The well-known concomitant poor intestinal adaptation 14 and the rapid gastric and intestinal transit described in these patients who have jejunostomies 15,16 prompted us to evaluate the effect of GLP-2 in this subgroup of short-bowel patients. As expected, none of the patients studied had a preserved meal-stimulated GLP-2 response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GLP-2 has received much attention as a potential therapeutic agent in the treatment of patients with short-bowel syndrome. In contrast to short-bowel patients with a preserved colon, patients with a jejunostomy have poor intestinal adaptation, 14 rapid gastric and intestinal transit, 15,16 and impaired postprandial GLP-2 secretion. 17 The present study evaluated the effects of subcutaneous GLP-2 administration on intestinal function in 8 patients with functional short-bowel syndrome and no colon in continuity and extensive resections of the small bowel.…”
Section: Background and Aimsmentioning
confidence: 96%
“…Limited information is available about degradation and absorption of milk proteins in SBS patients, 40 and besides differences in pH, also gastric emptying and transit time may influence effects of specific bioactive factors. In general, SBS is characterised by rapid gastric emptying 41 and short intestinal transit time. 42 Together these factors may have resulted in a low exposure of the intestinal epithelial lining to the bioactive factors in colostrum, and thus preventing their effects on intestinal adaptation beyond the effects induced by the additional nutrient input.…”
Section: Discussionmentioning
confidence: 99%
“…Only two jejunostomy patients and three patients with a retained colon were unable to work or help at home but they coped with their own treatment and went out occasionally. One patient with a jejunostomy and a hemiplegia was housebound and needed help with treatment (Nightingale, 1993).…”
Section: Rehabilitationmentioning
confidence: 99%